Tectonics, Dynamics, and Plio‐Pleistocene Magmatism in the Central Tyrrhenian Sea: Insights From the Submarine Transitional Basalts of the Ventotene Volcanic Ridge (Pontine Islands, Italy). (14th December 2020) - Conte, A. M.; Perinelli, C.; Bosman, A.; Castorina, F.; Conti, A.; Cuffaro, M.; Di Vincenzo, G.; Martorelli, E.; Bigi, S.
Abstract: In the Tyrrhenian back‐arc basin, the Ventotene Volcanic Ridge (VR) represents a NW‐SE‐oriented morphological high, located 25 km north of Ventotene Island in the Eastern Pontine Islands. It is considered part of an alignment of volcanic edifices developed in the central‐eastern Tyrrhenian Sea, from the western Pontine Islands (WPI) to the Campanian Volcanic Region. The samples dredged along the VR are basalts to trachybasalts belonging to the transitional (TR) rock‐series, with a 40 Ar‐ 39 Ar age of 2.760 ± 0.039 Ma. Petrological and geochronological data link the VR basalts to the TR peralkaline rhyolites cropping out at the WPI (∼1.6‐1.1 Ma); here, during a time span of ∼4.5‐1.0 Ma highly differentiated products of high‐potassium calc‐alkaline (HKCA, ∼4.5‐2.9 Ma) and K‐alkaline (KA, ∼1 Ma) series were also erupted. Notably, the parental melts of the three rock‐series were recognized in the continental slope close to the WPI (TR, HKCA) and eastward, namely in eastern Pontine Islands (KA), at the VR (TR), and in the Campanian Plain (HKCA). All the parental melts show typical orogenic geochemical signatures being originated from a similar heterogeneous suprasubduction mantle source, without the involvement of anorogenic sources. Tectonically, the faults bordering the VR, associated to the Pliocene E‐W directed rifting stage of the Tyrrhenian back‐arc basin were characterized by a more intense activity during the time span ∼5.0‐2.0 Ma (the emplacement time of HKCA and TR series), while KA products are related to a later stage of extension deformation (<∼2.0 Ma) when the extensional direction changed to NW‐SE and the VR fault activity decreased. Key Points: Under‐investigated seafloor sectors controlled by complex geodynamic processes The Ventotene Volcanic Ridge emplacement in a context of extensional deformations related to the opening of the Tyrrhenian back‐arc basin Coexistence in space and time of high‐K calc‐alkaline, transitional and K‐alkaline rock‐series sharing orogenic‐type signatures